Insights into Sustainable Food Systems: Learnings from Odisha’s Agricultural Officers - Junuthula, Shirisha; Kumari, Veenita (Journal of Agricultural Extension Management, 2025)
Sustainable food systems stand as pivotal pillars in addressing global food securitychallenges, emphasizing the need for environmentally conscious agricultural practices.Within this context, this research study delves into the realm of sustainable food systems,focusing on the invaluable insights gleaned from the dedicated cadre of Odisha’sAgricultural Officers. Their profound expertise and hands-on experience in agricultureform the bedrock of this investigation, offering a comprehensive understandingof sustainable agricultural practices and their implementation within the uniquelandscape of Odisha. The primary goal of this study is to unravel the intricate tapestryof sustainable agricultural practices through the lens of these proficient AgriculturalOfficers. Their perceptions, attitudes, and knowledge pertaining to crucial facetsof sustainable agriculture-ranging from soil health, water management, integratedpest management, to organic farming and more-serve as fundamental keystones inthis exploration. Through a structured methodology that involved pre-assessmentquestionnaires, exposure to sustainable agriculture concepts, and subsequent postassessment evaluations, this research uncovers the transformative learnings andevolving perspectives of these esteemed officers. Their wealth of experience and nuancedunderstanding of sustainable agricultural principles and challenges significantlycontributes to the broader discourse on achieving agricultural sustainability. By delvinginto the unique insights and experiences of Odisha’s Agricultural Officers, this studyaspires to shed light on actionable strategies and potential pathways to foster sustainablefood systems. Ultimately, these findings not only enrich the understanding of sustainableagriculture but also hold the promise of guiding future towards a more sustainable andresilient agricultural landscape in Odisha and beyond